1994
DOI: 10.1088/0029-5515/34/12/i04
|View full text |Cite
|
Sign up to set email alerts
|

Local magnetic shear control in a tokamak via fast wave minority ion current drive: theory and experiments in JET

Abstract: When an ion cyclotron resonance heating (ICRH) antenna array is phased (A$ # 0 or T), the excited asymmetric k,, spectrum can drive non-inductive currents by interaction of fast waves both with electrons (transit time magnetic pumping (e-TTMP) and Landau damping (e-LD)) and with ions at minority (fundamental) or harmonic cyclotron resonances, depending upon the scenario. On the basis of earlier theories, a simplified description is presented that includes the minority ion and electron current drive effects sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(113 citation statements)
references
References 18 publications
7
103
3
Order By: Relevance
“…It is shown that when a counterpropagating wave is deposited sufficiently accurately on the high field side, the fast ion effect is so strong that the internal kink mode is driven ideally unstable, and this in turn is consistent with the observed sawteeth [7,9] that are much shorter in period than those obtained in Ohmic plasmas. This should be contrasted with the classical [10] sawtooth control mechanism relating to the change in the magnetic shear, due to ICCD, which leads to a moderate effect on the threshold of an instability to resistive MHD (e.g., [19]), but with no realistic recourse to ideal instability. Furthermore, unlike the classical sawtooth control mechanism, the fast ion mechanism is independent of the electron drag, which is expected [20] to limit the current drive efficiency of the proposed ICRF system for ITER [21].…”
Section: Prl 102 065005 (2009) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
See 2 more Smart Citations
“…It is shown that when a counterpropagating wave is deposited sufficiently accurately on the high field side, the fast ion effect is so strong that the internal kink mode is driven ideally unstable, and this in turn is consistent with the observed sawteeth [7,9] that are much shorter in period than those obtained in Ohmic plasmas. This should be contrasted with the classical [10] sawtooth control mechanism relating to the change in the magnetic shear, due to ICCD, which leads to a moderate effect on the threshold of an instability to resistive MHD (e.g., [19]), but with no realistic recourse to ideal instability. Furthermore, unlike the classical sawtooth control mechanism, the fast ion mechanism is independent of the electron drag, which is expected [20] to limit the current drive efficiency of the proposed ICRF system for ITER [21].…”
Section: Prl 102 065005 (2009) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…Hence, hj 0 ðrÞi and hj 1 ðrÞi can be identified with, respectively, the passing and trapped ion currents, before the bulk plasma drag [10] has been subtracted. The asymmetry function cðr; y 2 Þ can be resolved if the passing ion current contribution is known.…”
Section: Prl 102 065005 (2009) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
See 1 more Smart Citation
“…b͒ Invited speaker. c͒ nificantly reduced by choosing 3 He minority ICRH, since the current dragged 16,13 by the background plasma tends to cancel the 3 He current in the relevant region of the tokamak ͑provided that the effective charge of the plasma is close to that of 3 He, where Z ef f Ͻ 2 typically͒. It is shown that sawtooth control employing low concentration minority 3 He is nevertheless effective, thus strengthening the likelihood of the dominant effect of the fast ion mechanism, 9 and moreover, demonstrating the viability of sawtooth control using ICRH in ITER, 1 which is primarily and routinely expected to employ 3 He minority.…”
Section: Introductionmentioning
confidence: 99%
“…5). The sawtooth period has been varied in ICRF-only discharges by more than one order of magnitude due to changes in the magnetic shear near q = 1, using hydrogen minority (ω ≈ ω cH ) ICCD [18][19][20][21]. Experiments have also been carried out with directed ICRF waves tuned to the second harmonic hydrogen resonance (ω ≈ 2ω cH ) to affect the sawtooth period and amplitude in discharges with ICRF only and in discharges with combined ICRF and NBI [3,[22][23][24].…”
Section: Modifications Via Ion Cyclotron Current Drivementioning
confidence: 99%